Global analysis of groundwater pumping from increased river capture - Inge E M de Graaf; Bryan Marinelli; Sida Liu (Environmental Research Letters, 2024)
In many regions globally, groundwater overuse exceeds natural replenishment, leading to immediate consequences such as reduced river flows and devastating impacts on freshwater ecosystems. In alluvial aquifers in particular, groundwater pumping contributes to river flow reduction in two significant ways: first, by intercepting water that would naturally discharge into the river, and second, by lowering groundwater levels below the riverbed, causing river water to infiltrate. Despite these critical interactions, large-scale water resources assessments often overlook the relationship between groundwater and surface water, hindering a comprehensive understanding of the consequences of groundwater pumping on both the groundwater and surface water systems. Our study, utilizing a coupled global-scale groundwater–surface water model, reveals that approximately 20% of globally pumped groundwater stems from diminished streamflow, while 16% results from reduced storage. Projections for the end of the century, accounting for climate change, suggest potential increases to 30% from reduced streamflow and a decrease to 12% from reduced storage. Notably, our results highlight that the impact on streamflow is more widespread and linked to smaller pumping rates, contrasting with impacts on storage associated with higher pumping rates. This study shows the crucial need to include groundwater–surface water interactions in large-scale water resources assessments, not only for accurate estimates of freshwater availability but also for a comprehensive understanding of the far-reaching impacts of groundwater overuse related to increasing water demands and climate change.